Biochemical and Structural Characterization of Mycobacterium tuberculosis β-Lactamase (BlaC) with the Carbapenems Ertapenem and Doripenem - Tremblay, Lee W. (2010)
Despite the enormous success of β-lactams as broad-spectrum antibacterials, they have never been widely used for the treatment of TB due to intrinsic resistance that is caused by the presence of a chromosomally-encoded gene (blaC) in Mycobacterium tuberculosis. Our previous studies of TB BlaC revealed that this enzyme is an extremely broad-spectrum β-lactamase hydrolyzing all β-lactam classes. Carbapenems are slow substrates that acylate the enzyme but are only slowly deacylated and can therefore act also as potent inhibitors of BlaC. We carried out the in vitro characterization of doripenem and ertapenem with BlaC. A steady-state kinetic burst was observed with both compounds with magnitudes proportional to the concentration of BlaC used. The results show apparent K(m) and k(cat) values of 0.18 µM and 0.016 min(−1) for doripenem and 0.18 µM and 0.017 min(−1) for ertapenem. FTICR mass spectrometry demonstrated that the doripenem and ertapenem acyl-enzyme complexes remain stable over a time period of 90 min. The BlaC-doripenem covalent complex obtained after 90 minutes of soaking was solved to 2.2 Å, while the BlaC-ertapenem complex obtained after a 90 minute soak was solved to 2.0 Å. The 1.3 Å diffraction data from a 10 minute ertapenem-soaked crystal revealed an isomerization occurring in the BlaC-ertapenem adduct in which the original Δ(2) pyrroline ring was tautomerized to generate the Δ(1) pyrroline ring. The isomerization leads to the flipping of the carbapenem-hydroxyethyl group to hydrogen bond to the carboxyl O2 of Glu166. The hydroxyethyl flip results in both decreased basicity of Glu166 and in a significant increase in the distance between the carboxyl O2 of Glu166 and the catalytic water molecule, slowing hydrolysis.